2003
DOI: 10.1016/j.neuron.2003.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B2 and EphB1 Mediate Retinal Axon Divergence at the Optic Chiasm

Abstract: In animals with binocular vision, retinal ganglion cell (RGC) axons either cross or avoid the midline at the optic chiasm. Here, we show that ephrin-Bs in the chiasm region direct the divergence of retinal axons through the selective repulsion of a subset of RGCs that express EphB1. Ephrin-B2 is expressed at the mouse chiasm midline as the ipsilateral projection is generated and is selectively inhibitory to axons from ventrotemporal (VT) retina, where ipsilaterally projecting RGCs reside. Moreover, blocking ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
382
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(403 citation statements)
references
References 50 publications
16
382
0
Order By: Relevance
“…2c). This discrete region of the subventricular zone and cortex is thought to represent projecting radial glia (Shu et al, 2003b;Williams et al, 2003), which was confirmed by immunohistochemistry with the radial glia marker anti-RC1 (Fig. 2d).…”
Section: Expression Of Ephrins In the Developing Forebrainmentioning
confidence: 58%
“…2c). This discrete region of the subventricular zone and cortex is thought to represent projecting radial glia (Shu et al, 2003b;Williams et al, 2003), which was confirmed by immunohistochemistry with the radial glia marker anti-RC1 (Fig. 2d).…”
Section: Expression Of Ephrins In the Developing Forebrainmentioning
confidence: 58%
“…All EphB mutant mice were previously described (23)(24)(25)44). EphrinB1 loxp and EphrinB2 loxp cKO mice were previously described (32,45).…”
Section: Methodsmentioning
confidence: 99%
“…Retinal ganglion cells in the ventrotemporal retinal crescent project ipsilaterally, whereas ganglion cells outside of the ventrotemporal retina and some late-born cells in the ventrotemporal retina project contralaterally (Godement et al 1990;Guillery et al 1995). In both the frog and mouse, ephrinBs expressed by glial cells at the midline force ventrotemporal retinal ganglion cell axons expressing EphB receptors to the ipsilateral side of the chiasm (Nakagawa et al 2000;Williams et al 2003). The timing of receptor and ligand expression and subsequent downregulation is exquisite (Williams et al 2003).…”
Section: Distribution and Regulation Of Guidance Receptors And Cuesmentioning
confidence: 99%
“…In both the frog and mouse, ephrinBs expressed by glial cells at the midline force ventrotemporal retinal ganglion cell axons expressing EphB receptors to the ipsilateral side of the chiasm (Nakagawa et al 2000;Williams et al 2003). The timing of receptor and ligand expression and subsequent downregulation is exquisite (Williams et al 2003). The transcription factor Zic2 regulates EphB1 expression in ventrotemporal retinal ganglion cells, it is required for the ipsilateral projection, and it is sufficient to induce an ipsilateral…”
Section: Distribution and Regulation Of Guidance Receptors And Cuesmentioning
confidence: 99%